2019
DOI: 10.1016/j.healthplace.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Food play: A novel research methodology for visceral geographers and health researchers

Abstract: This paper reinforces the value of visceral geographic approaches to health research as a method 'beyond talking'. The paper establishes and sets out an integrative embodied multi-sensory research methodology-food play. Researchers across the social sciences and sciences are exploring the limits of logo and researcher centric research methods and exploring peoples sensory experience of themselves and the wider world using participatory, patient-centred, multi-sensory, visceral and biosocial geographic approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Often, families participated in these experiences together, as well as alongside holiday club staff and other families who also attended. Importantly, face-to-face sessions additionally allowed for families to become immersed in multi-sensory experiences with food, including tasting, smelling, and touching often unfamiliar ingredients, which prior research has demonstrated to be successful in other contexts [ 25 , 26 ]. Multi-sensory exposure has been found to increase children’s willingness to try and taste vegetables [ 27 ], and similarly, HAF leads highlighted that these multi-sensory sessions were extremely engaging, and perceived participation to enhance families’ willingness to try the foods involved.…”
Section: Discussionmentioning
confidence: 99%
“…Often, families participated in these experiences together, as well as alongside holiday club staff and other families who also attended. Importantly, face-to-face sessions additionally allowed for families to become immersed in multi-sensory experiences with food, including tasting, smelling, and touching often unfamiliar ingredients, which prior research has demonstrated to be successful in other contexts [ 25 , 26 ]. Multi-sensory exposure has been found to increase children’s willingness to try and taste vegetables [ 27 ], and similarly, HAF leads highlighted that these multi-sensory sessions were extremely engaging, and perceived participation to enhance families’ willingness to try the foods involved.…”
Section: Discussionmentioning
confidence: 99%
“…The design is theory-based and is created by gathering, analyzing, and presenting the data. Hence, the design enabled the researcher to provide insights into the reasons for the research while allowing for the answering of the research question [17]. A major advantage that justi es the choice of descriptive research design is that the participants were investigated in their natural environment.…”
Section: Methodsmentioning
confidence: 99%
“…The reflective process used by the Altered Eating Research Network’s ‘food play’ methodology (Burges Watson et al, 2019) may be one approach through which to reflect on the biosociality of food and eating and to encourage new food associations. Food play is defined as a ‘hands-on experience of food preparation, sharing and “tasting opportunities” (where tasting is not essential to involvement) in a commensal setting where the research focus is co-produced with participants’ (2019: 140).…”
Section: Sensing the Future: Engaging With Food Through Flavour?mentioning
confidence: 99%